Generating string solutions in BTZ - David, Justin R.; Kalousios, Chrysostomos [UNESP]; Sadhukhan, Abhishake (Springer Nature, 2013)
Integrability of classical strings in the BTZ black hole enables the construction and study of classical string propagation in this background. We first apply the dressing method to obtain classical string solutions in the BTZ black hole. We dress time like geodesics in the BTZ black hole and obtain open string solutions which are pinned on the boundary at a single point and whose end points move on time like geodesics. These strings upon regularising their charge and spins have a dispersion relation similar to that of giant magnons. We then dress space like geodesics which start and end on the boundary of the BTZ black hole and obtain minimal surfaces which can penetrate the horizon of the black hole while being pinned at the boundary. Finally we embed the giant gluon solutions in the BTZ background in two different ways. They can be embedded as a spiral which contracts and expands touching the horizon or a spike which originates from the boundary and touches the horizon. © 2013 SISSA, Trieste, Italy.
Keywords: AdS-CFT Correspondence; Black Holes; Integrable Equations in Physics